2009
DOI: 10.3892/ijo_00000354
|View full text |Cite
|
Sign up to set email alerts
|

TCDD mediates inhibition of p53 and activation of ERα signaling in MCF-7 cells at moderate hypoxic conditions

Abstract: Abstract. TCDD (2,3,7, is known to promote cancer initiation and progression and accumulates in mammary fat tissue. Effects of TCDD are mediated by the aryl hydrocarbon receptor (AhR). Physiological conditions of moderate hypoxia in breast cancer also activate another transcription factor, hypoxia-inducible factor-1 alpha (HIF-1·). In addition, the transcription factors p53 and the estrogen receptor alpha (ER·) are important key players in breast cancer progression. Here, human breast cancer cells cultured und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Administration of dioxins (especially TCDD) to pregnant rats leads to structural abnormalities in the development of their pups’ mammary tissues and higher incidence of tumors when the pups grow to adulthood [ 500 504 ]. TCDD may exert its cancer-causing effects both by decreasing the efficacy of tumor-suppressor mechanisms and by enhancing the estrogenic signaling within the mammary cells [ 505 ].…”
Section: Evidence Linking Environmental Factors and Breast Cancermentioning
confidence: 99%
“…Administration of dioxins (especially TCDD) to pregnant rats leads to structural abnormalities in the development of their pups’ mammary tissues and higher incidence of tumors when the pups grow to adulthood [ 500 504 ]. TCDD may exert its cancer-causing effects both by decreasing the efficacy of tumor-suppressor mechanisms and by enhancing the estrogenic signaling within the mammary cells [ 505 ].…”
Section: Evidence Linking Environmental Factors and Breast Cancermentioning
confidence: 99%
“…Our previous clinical data and tumor cell analysis showed that high AHR expression was associated with low tumor suppressor protein (p53 and RB) expression but higher proto‐oncogene ( ISX, CCND1 , and E2F1 ) expression in vitro and in vivo . Although the detailed mechanisms underlying differential HCC prognostic outcomes remain unclear, AHR overexpression has been shown to inhibit p53 expression and activity in various cell lines and animal models, thereby contributing to tumor progression . Furthermore, AHR has been shown to interact with RB in various tumor cell lines, where it triggers E2F1 release and promotes cell cycle progression .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of evidence for DEN as an AHR ligand or AHR pathway metabolite, the chemical structure of DEN is homologous to polyromantic diphenyl ethers, the ligands of AHR. Although the actual role of AHR in tumorigenesis remains to be elucidated, the contribution of AHR to cancer progression or prevention may depend on the procarcinogen activation/detoxification balance and AHR expression in a cell‐specific manner . Further in‐depth research is needed to clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations